Determination of nickel in fuel ethanol using a carbon paste modified electrode containing dimethylglyoxime - Oliveira Tartarotti, Fernando; Firmino de Oliveira, Marcelo; Roberto Balbo, Valdir; Ramos Stradiotto, Nelson (Springer, 2006)
A mercury-free electrode chemically modified with carbon paste containing dimethylglyoxime was used for determination of nickel in fuel ethanol. The instrumental parameters and composition of the modified paste were optimized. The analytical curve for nickel determination from 5.0 x 10(-9) to 5.0 x10(-7) mol(-1) was obtained using 25 min of accumulation time. The detection limit and amperometric sensitivity obtained for this method were 2.7 x 10 mol(-1) and 5.2 x 10(8) mu A mol(-1) L, respectively. The values for nickel concentration in four commercial samples of fuel ethanol were obtained in the range of 1.1 x 10(-8) to 6.9 x 10(-8) mol(-1). A comparison to graphite furnace atomic absorption spectrometry (GFAAS) was performed for nickel determination in commercial samples of ethanol.
Keywords: nickel; fuel ethanol; chemically modified electrode; dimethylglyoxime; differential pulse voltammetry